Perencanaan SDM dengan Peningkatan Keterlibatan (Employee Engagement) dan Kepuasan Kerja Karyawan - Angela Vidy Octaviani; Ellen Aryanta; Fitriah Rohmiyanti; Muhammad Zein Saleh (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study analyzes the strategic role of Human Resource Planning (HRP) in enhancing employee engagement and job satisfaction as critical determinants of organizational sustainability in a rapidly changing economic and technological environment. Increasing competition, digital transformation, and workforce uncertainty require organizations to shift HR planning from a purely administrative function toward a human-centric and strategic approach. This paper employs a qualitative literature review by synthesizing established theories and recent empirical studies on HR planning, employee engagement, and job satisfaction. The findings indicate that effective HR planning aligns workforce quantity and quality with future organizational needs while simultaneously addressing psychological factors such as motivation, emotional attachment, and perceived fairness. Proper workforce planning contributes to higher employee engagement by balancing job demands with adequate resources, leadership support, and opportunities for learning and development. Moreover, job satisfaction functions as a foundational element that strengthens engagement, reduces turnover intentions, and improves employee productivity. In the Indonesian context, where structural labor challenges and productivity gaps remain prevalent, integrating HR planning with engagement and satisfaction strategies becomes increasingly important. This study contributes theoretically by reinforcing the interrelated nature of HR planning, employee engagement, and job satisfaction, and practically by offering insights for organizations to design adaptive, data-driven, and sustainable human resource strategies that support long-term performance and employee well-being.